WHY DO THE UNIVERSITY GRADUATES SETTLE DOWN IN THE UNIVERSITY TOWN? POTENTIAL IMPLICATIONS FOR CITY MARKETING -THE CASE OF CRACOW - Sebastian Brańka (Polityki Europejskie, Finanse i Marketing)
The background of the paper is place marketing, as a concept of territorial unit management aimed at customer satisfaction. In the paper it was underlined that one of the key factors that contemporary cities need for their development is human capital. Furthermore the author of the paper refers to place marketing publications to present the idea of city markets, where cities compete for gaining necessary resources. It is worth mentioning that the current competition between the cities is of global range. Therefore investors, new residents and tourists (being major markets for the cities to compete) choose cities from all over the world to meet their expectations. In the article special stress is made on students as a potential source of city’s new inhabitants. In the consecutive parts of the paper the author introduces the conclusions from a 2011 research supervised by the author and conducted on a significant group of students of Cracow University of Economics. The purpose of the research project was to identify the factors increasing attractiveness of the city for settling down after university graduation. The students were asked on their plans regarding their permanent residence after graduation and factors stimulating the decision to stay in the same city.